ANALYSIS OF HAND HYGIENE PRACTICES AMONG HEALTH CARE WORKERS FOR PREVENTION OF NOSOCOMIAL INFECTION: A SYSTEMATIC REVIEW - Juliana, Mutia; M.G Sianipar, Imelda; Aditya Willyanto, Nathan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Hand hygiene has been regarded as the most efficient technique in nosocomial infections control.Aim: This study aims to summarize and evaluate the impact of hand hygiene practices among health care workers for prevention of nosocomial infection.Methods: A systematic search strategy was conducted across several electronic reference databases (PubMed, Cochrane Library, Google Scholar) and included articles published between 2019–2023. Duplicate publications, review articles, and incomplete articles were excluded.Results: The databases search identified a total of 19.427articles (Table 1). Of these, 120 articles passed the screening process, resulting in 20 articles for full-text assessment. Among them, 13 articles contain insufficient details regarding the focus of interest. Hence, we found 7 appropriate studies.Conclusion: Our study found that hand hygiene practices is a preventive measure for NIs and it seems that hand rubbing appeared to be more effective than hand washing as a hand-hygiene strategy, albeit with evidence of low to moderate quality. This strategy promotes the use of hand-rubbing in intensive care units for improved clinical outcomes for patients and healthcare providers.